Spectroelectrochemical Study Revealing the Redox Potential of Human Monoamine Oxidase a - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Ltd, 2019)
Spectroelectrochemical measurements were performed on human monoamine oxidase A (MAO A) at pH 7.8, and the redox potential of the enzyme was determined. MAOs are membrane-bound flavoenzymes that catalyse the oxidation of different neurotransmitters such as dopamine, serotonin or norepinephrine. As redox-active cofactor the enzymes contain a covalently bound 8α-S-cysteinyl-flavin adenine dinucleotide (8α-S-cysteinyl-FAD). The spectroelectrochemical measurements were performed in the presence of various one- and two-electron transferring redox mediators such as viologens and 1,4-naphthoquinones. No singly reduced flavosemiquinone radical anion or radical could be detected in the timescale of the experiment, i.e. the enzyme changes from the fully oxidized flavoquinone to the fully reduced flavohydroquinone. A redox potential of −177 ± 4 mV vs. NHE was determined at pH 7.8. Neither the ionic strength of the buffer, nor the composition of the mediator mixture, nor the passivation of the gold capillary electrode surface by chemisorption of mercaptohexanol had any influence on the values determined for the redox potential. © 2019 Elsevier Ltd